Prevalence, Correlates and Treatment Needs of Dental Caries Among People on Antiretroviral Therapy in Uganda: A Cross Sectional Study - Arubaku, Wilfred; Kwizera, Godfrey; Tusubira, Deusdedit; Kanyesigye, Michael; Chamut, Steffany; Seymour, Brittany Anne; Siedner, Mark J.; Niyonzima, Vallence; Najjuma, Josephine N.; Maling, Samuel (Research square, 2022)
Background: Oral diseases are estimated to affect half of people living with HIV in the global north, and are often marked by pain, discomfort, disfigurement and reduced quality of life. Both HIV-specific and antiretroviral therapy-associated oral diseases have been found in this population. However, the association between antiretroviral therapy use and dental caries has not been well described in rural Africa where majority of people living with HIV reside, and where health behaviors and access to dental care vary significantly from the global north. Methods:A cross-sectional study was conducted among PWH attending a high volume HIV clinic with an enrollment of 10,000 patients in a regional referral hospital in Southwestern Uganda. The clinic is located in an urban setting with a large rural catchment area. Oral health data was collected using the modified World Health Organization oral health questionnaire for adults. Dental examinations were conducted to identify and classify dental caries using the decayed, missing, filled, teeth (DMFT) index and compute the treatment need. Logistic regression models were employed to identify correlate of dental caries. Results: A total of 194 participants were included in the study. The majority were females (124/194, 63.9%) with a median age of 42 years (IQR 36-49). The prevalence of dental caries experience among individuals on ART was 67%, (130/194), 95% CI (60-75%). The mean DMFT index score was 4 (IQR 2-6) and treatment need was 96%. A higher CD4 count was associated with the presence of dental caries (OR 0.403, 95% CI (0.175-0.932) although it was not significant at multivariate analysis. Conclusion: There is a high prevalence of dental caries among PWH on ART in Uganda. Our data demonstrate a high oral treatment need among the participants. We recommend inclusion of preventive and therapeutic oral care into HIV care in this region.
Keywords: Dental caries; Antiretroviral therapy; HIV; Oral diseases